A clinical and ultrasound study on the use of postplacental intrauterine device - João Henrique Araújo Fernandes; Umberto Gazi Lippi (Einstein (São Paulo), 2004)
Objective: To evaluate the relation of postplacental intrauterinedevice insertion immediately after vaginal delivery and cesareansection and its effects on the following: continuation, expulsionrate and eventual removals. To verify if ultrasound is an adequatemethod to follow-up postplacental IUD insertions. To assess if theimmediate insertion of postplacental IUD leads to an increasedrisk of uterine infections and perforations, or greater likelihood ofpregnancy during the observation period. Methods: A group of 50patients who had an intrauterine device introduced within tenminutes after delivery of the placenta were studied. Twenty-fivewomen had vaginal delivery and 25 had cesarean sections. Theintrauterine device used in this study was the Multiload CU 375,standard model, manufactured by Organon Ltd., in Ireland. Theintrauterine device was inserted in those who had vaginal deliveryeither manually and under anesthesia, or with an inserter, whichdid not require anesthesia. In patients who had cesarean sections,the insertion was manual. Clinical and ultrasound follow up wasperformed four times: 48 hours postpartum, and at 6, 12 and 24weeks. The distance from the top of the intrauterine device to theuterine fundus was measured by ultrasound. Results: This studyshowed a significant difference in postplacental intrauterinedevices inserted after vaginal deliveries and cesarean sections.The expulsion/removal rate was 32% among the subjects who hadan intrauterine device inserted after vaginal delivery. There wereno expulsions or removals in those submitted to cesarean sections.In the control ultrasound of intrauterine devices inserted aftervaginal delivery, at 6 weeks, the distance of 10 mm from the top ofthe device to the fundus was an average standard measurementto determine continuation (distance < 10 mm, the IUD wouldremain in the uterus) and expulsion/removal (distance > 10 mm,the IUD would be expelled or be removed). There were no cases ofuterine infections or perforations, and no pregnancies during thecourse of this study. Conclusions: Postplacental intrauterine deviceinsertion showed to be an useful and safe contraceptive method.The ultrasound demonstrated to be a useful and reliable method tocontrol postplacental intrauterine device insertions.